Work Motivation, Discipline, and Competency Patterns in Employee Performance: Motivasi Kerja, Disiplin, dan Pola Kompetensi dalam Kinerja Karyawan - Rizky Hari Setiawan; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Employee performance is a central concern for organizations seeking sustainable productivity and operational efficiency. Specific Background: Work motivation, work discipline, and work competency are frequently identified as key internal factors shaping employee performance, yet their combined patterns remain context-dependent. Knowledge Gap: Previous studies report mixed findings regarding the relative contribution of these variables, particularly within small and medium-sized enterprises. Aims: This study aims to examine the relationships between work motivation, work discipline, work competency, and employee performance at UD Alfa Furnitur. Results: Using a quantitative approach with data from 100 employees analyzed through SEM-PLS, the findings indicate that work motivation, work discipline, and work competency each demonstrate positive and statistically significant relationships with employee performance. Among these variables, work motivation shows the strongest association. Novelty: This study provides empirical evidence from a furniture manufacturing context by integrating three internal employee factors within a single structural model. Implications: The findings suggest that organizations should prioritize motivational strategies alongside disciplinary consistency and competency development to support sustainable employee performance. Keywords: Work Motivation, Work Discipline, Work Competency, Employee Performance, SEM-PLS Key Findings Highlights: Motivation-related indicators show the strongest statistical association with performance outcomes. Consistent disciplinary practices align with higher employee work results. Employee competencies support performance through knowledge and skill alignment.